Comprehensive evaluation of maize germplasm for alkali tolerance during germination - Pan, Zhuyun; Ge, Zhiqiang; Gao, Fengming; Ao, Man; Guan, Yixin (Frontiers in Plant Science, 2026)
IntroductionAlkaline stress poses a major challenge to crop productivity, often causing more severe physiological damage than saline stress alone. Maize is particularly sensitive to alkaline conditions, which significantly inhibit germination and early growth. The establishment of accurate evaluation systems for alkali tolerance is therefore crucial for the development of resilient cultivars.MethodsA total of 42 maize germplasm accessions were evaluated under simulated alkaline stress (100 mM) during germination. A comprehensive analytical framework integrating principal component analysis, membership function analysis, stepwise regression, cluster analysis, and discriminant analysis was used to assess alkalinity tolerance. The Lindeman–Merenda–Gold method was further employed to quantify the relative contribution of each morphological trait to the comprehensive alkali tolerance score.ResultsAlkaline stress significantly inhibited early seedling growth, and several germination-related traits showed strong associations with alkali tolerance. Based on the comprehensive D value, the maize accessions were classified into five tolerance groups. Trait contribution analyses consistently indicated the germination index (GI) and the shoot dry weight (SDW) as the strongest determinants of tolerance, with root length (RL) and root fresh weight (RFW) also playing notable roles. These indicators form a reliable basis for the screening of alkali-tolerant maize germplasm, providing a foundation for future refinement of the evaluation system through physiological or molecular approaches.DiscussionThis integrated evaluation system effectively distinguishes maize germplasm by alkali tolerance level and identifies key morphological determinants. The findings provide a scientific basis for germplasm screening and breeding of alkali-tolerant maize materials, contributing to sustainable agricultural production in saline–alkaline environments.